Fermentasi Jerami Padi Dengan Berbagai Probiotik Terhadap Kandungan Selulosa, Hemiselulosa Dan Lignin - Bahri, Syamsul (Jambura Journal of Chemistry, 2025)
ABSTRACT Utilization of rice straw is one way of addressing the demand for ruminant feed, and requires management before it is used for livestock through suffering. This study aims to determine the content of cellulose, hemicellulose and lignin fermented rice straw with various probiotics This research aimed to determine the contents of cellulose, hemicellulose, and lignin in rice straw fermented with various probiotics. It employed a completely randomized design (CRD) with five treatments and three replications. The treatments consisted of: PO = 90% rice straw + 10% concentrate, P1 = 90% rice straw + 10% concentrate + Bio EM+ probiotic, P2 = 90% rice straw + 10% concentrate + starbio probiotic, P3 = 90% rice straw + 10% concentrate + win prob probiotic, P4 = 90% rice straw + 10% concentrate + a combination of probiotics (Bio EM+, starbio and win prob). Furthermore, the parameters measured were the contents of cellulose, hemicellulose, and lignin. The findings depicted that the treatment had a highly significant effect (P